Improving metacognitive skills using problem based learning (pbl) at natural science of primary school in deli serdang, indonesia - Anggi Tyas Pratama (Universitas Negeri Jakarta, 2018)
Metacognitive skills are one of the skills needed in a 21st century lesson in science learning. Empowerment of thinking and metacognitive skills needs to be done so that learners become independent learners. Metacognitive skills are influenced by learning strategies. This PBL strategy in learning is expected to help students to improve students' metacognitive abilities in science learning.This study aims to determine the improvement of metacognitive skills of students who are taught with PBL strategies. The results showed that PBL strategies can improve students' metacognitive skills on different abilities. The students' metacognitive improvement on PBL strategy is 73.93% and conventional is 59.51%. PBL strategy can be used in science learning to improved metacognitive skill in Deli Serdang.